LINGUO-CULTURAL PROBLEMS OF TRANSLATION (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the linguo-cultural problems that arise during the translation process, emphasizing the challenges faced by translators when navigating between languages and cultures. It highlights key issues such as equivalence, the translation of idiomatic expressions, politeness and formality, cultural context, and humor. The article discusses how these factors complicate the task of translating not just the words, but the underlying cultural nuances, values, and social norms embedded in the original text